Epidemiology of Enteric Disease in C-EnterNet’s Pilot Site – Waterloo Region, Ontario, 1990 to 2004 - Victoria A Keegan; Shannon E Majowicz; David L Pearl; Barbara J Marshall; Nancy Sittler; Lewinda Knowles; Jeffery B Wilson (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: The objective of the present study was to describe the epidemiology of reportable enteric illness in Ontario’s Waterloo region, including comparing calculated incidence rates with published rates, and adjusting for under-reporting to determine the number of community cases, where published data were available.